PENGEMBANGAN METODE PEMBELAJARAN KEWIRAUSAHAAN BERBASIS PRAKTIK UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA MAHASISWA PRODI ADM BISNIS POLMED - ika mary pasaribu; safaruddin safaruddin (Universitas Dharmawangsa, 2023)
Entrepreneurship is a science that can be studied and applied, especially in universities. In fact, there are not a few entrepreneurship courses that have been studied in tertiary institutions but have had no impact on students who have completed them other than simply getting grades. So what must be implemented so that the entrepreneurship course that has been completed by the final year students can be applied, not just finished with the mere acquisition of grades. Given the importance of entrepreneurship, facing the global economy and the increasing difficulty of finding jobs for today's university graduates. Students as potential successors to the nation to build the country must think and choose whether aftergraduating from college they will look for work or create jobs. If we observe as Educators, mostly after graduating from college, Alumni compete to find jobs that are in accordance with their fields, rather than entrepreneurship. To achieve the aims and objectives that have been determined, the expected research targets are: 1) The creation of an interest in entrepreneurship from students and entrepreneurship can be created from the educational path. 2) The creation of a new practice-based learning method for entrepreneurship courses that is efficient in delivering entrepreneurship material. 3) The creation of university graduates who are able to create jobs who have an interest in entrepreneurship without having to wait for jobs.Key Word: Metode Pembelajaran berbasis praktik, Minat berwirausaha